Ketamine administration during adolescence impairs synaptic integration and inhibitory synaptic transmission in the adult dentate gyrus - Santander, Odra (2025)
Ketamine administration during adolescence affects cognitive performance; however, its long-term impact on synaptic function and neuronal integration in the hippocampus a brain region critical for cognition remains unclear. Using functional and molecular analyses, we found that chronic ketamine administration during adolescence exerts long-term effects on synaptic integration, expanding the temporal window in an input-specific manner affecting the inner molecular layer but not the medial perforant path inputs in the adult mouse dorsal hippocampal dentate gyrus. Ketamine also alters the excitatory/inhibitory balance by reducing the efficacy of inhibitory inputs likely due to a reduction in parvalbumin-positive interneurons number and function. These findings indicate that during adolescence, ketamine exerts a strong effect on inhibitory synaptic function mediated by parvalbumin-positive neurons that ultimately impact synaptic integration in the dorsal adult dentate gyrus, which could help to understand the neurobiological and functional bases that confer greater vulnerability to the adolescent brain.